Effect of alkaline diagenesis on sandstone reservoir quality: Insights from the Lower Cretaceous Erlian Basin, China. Issue 2 (March 2020) - Li, Shengyu; Tian, Jingchun; Lin, Xiaobing; Zuo, Yinhui; Kang, Hua; Yang, Dongdong
The Tengger Formation in the Baiyinchagan sag of the Erlian Basin has behaved as a low-permeability petroleum system during its diagenetic history. Through the observation and examination of thin section, scanning electron microscopy, and X-ray diffraction data, this study found the existence of alkaline diagenesis, as indicated by the dissolution of quartz, the precipitation of authigenic illite and chlorite, and the formation of carbonate and authigenic albite cements. There were two types of alkaline diagenetic conditions: the early alkaline diagenetic conditions were controlled by the syndepositional environment, and the multiphase burial alkaline diagenetic conditions were controlled by the evolution of organic acids and thermal fluids. The quantitative model of the evolution of porosity over geologic time developed in this study indicates that quartz dissolution increased the porosity by a total of 0.85%. This work may provide significant advances in the understanding of the low-permeability reservoirs in the Erlian Basin and lays the scientific foundation for oil and gas exploitation.